Faktor Penyebab Kemiskinan Nelayan Tradisional - Hamdani, Haris; Wulandari, Kusuma (University of Jember, 2016)
Abstract Bali strait waters is an area of ??over fishing (fishing waters) as well as an abundant supply of fish, especially Lemuru, +80 % of all the total fish which is caught by fishermen. Besides, Kedungringin is also being a fishing area for traditional fishermen. With the condition of over fishing and supporting with the good condition of the coral reef in the Bali strait, it seems the traditional fishermen community in Kedungringin should be more prosperous. The purpose of this study is to describe and analyze the causes of poverty in the traditional fishing village of Kedungringin, Muncar, Banyuwangi. This research uses descriptive method with qualitative approach. Informants who involved are principal informants and additional informants. The principal informants are traditional fishermen who live in Kedungringin who still suffer from poverty and still struggling to meet their daily needs. Then, additional informants are a wife of the fisherman, village chief and ‘pengamba’ (fish sellers). Method of observation, interviews and documentation is chosen as a data collection method. Meanwhile, the analysis uses an interactive model of data reduction data presentation drawing conclusions or verification. The causes of poverty in the traditional fishing communities due to the low education, the role of economic institutions, the habits of fishermen, the alternative employment, the ownership of capital, as well the technology used.